The Prevalence of Second Victim Syndrome and Emotional Distress in Pediatric Intensive Care Providers - Wolf, Michael; Smith, Kathleen; Basu, Mohua; Heiss, Kurt (Journal of Pediatric Intensive Care, 2021)
Pediatric critical care providers are at higher risk of second victim syndrome (SVS) and emotional distress after a poor patient outcome, unanticipated adverse event, medical error, or patient-related injury. We sought to determine the prevalence of SVS within our intensive care units (ICUs) and evaluate the adequacy of current institutional peer support. A validated survey tool, the second victim experience and support tool was sent electronically to all ICU providers in our pediatric health care system. Of 950 recipients, there were 266 respondents (28%). Sixty-one per cent of respondents were nurses; 19% were attending physicians, advanced practice providers, and fellows; 88% were females; 42% were aged 25 to 34 years; and 43% had worked in the ICU for 0 to 5 years. The most common emotion experienced was psychological distress (42%) and one-third of respondents questioned their self-efficacy as a provider after a second victim event. Support from colleagues, supervisors, and the institution was perceived as low. Support from a respected peer was the most desired type of support by 81% of respondents. Emotional distress and SVS are commonly found among pediatric ICU providers and the level of support is perceived as inadequate. Developing and deploying a peer support program are crucial to staff's well-being and resilience in the high-stress ICU environment.
Keywords: second victim syndrome; medical error; burnout; peer support; ICU; pediatric